A Multicomponent Particle Model and Linear Fitting Calibration Method for Heterogeneous Rocks. (1st April 2019) - Guo, Qifeng; Zhang, Ying; Xi, Xun; Wu, Xu; Cai, Meifeng
Abstract : Deformation and failure of rock are very important to underground space engineering. In this paper, a new three-dimensional multicomponent bonded-particle model is developed for heterogeneous rocks. Granite samples from the Sanshandao Gold Mine are first analyzed using a microscope. Cylindrical and disc models consisting of four minerals (i.e., plagioclase, potash feldspar, quartz, and biotite) are built to simulate the behavior of the granite under compressive and tensile tests. To improve the calibration efficiency, a new method for determining the microparameters of minerals is proposed. Uniaxial compression, triaxial compression, and Brazilian tests are carried out in the lab. The failure pattern and stress-strain curves are obtained from numerical simulations and verified with those observed in the experiments. Furthermore, the Mohr–Coulomb and Hoek–Brown strength parameters are obtained and compared with the experimental results. The multicomponent particle model is shown to well reproduce the behavior of granite under the compressive and tensile tests. The multicomponent bonded-particle model significantly improves the accuracy of three parameters: the ratio of tensile strength to uniaxial compressive strength, the friction angle, and the parameter m i of the Hoek–Brown criterion. The linear fitting calibration method provides a fast and efficient way to determine the microparameters of particles in heterogeneous rocks.